Prevalence of Common Metabolic Bone Diseases Diagnosed by Dual-Energy X-Ray Absorptiometry Scanning and Blood Test in Outpatients With Osteoarthritis the Knee - Napat Chaiyavech MD; Satit Thiengwittayaporn MD; Natthapong Hongku MD, MSc (Geriatric Orthopaedic Surgery & Rehabilitation, 2024)
Introduction Osteoarthritis of the knee (OA knee) is a common geriatric disease that require total knee arthroplasty. Periprosthetic fracture is one of the common complications, which is strongly related to metabolic bone disease. Materials and methods We conducted a prospective study on 291 outpatients with OA knee between November 2020 and April 2021. Baseline characteristics, dual-energy X-ray absorptiometry and blood test results were analysed using logistic regression analysis and expressed as odds ratio, 95% confidence intervals and P -values. Results Overall metabolic bone diseases were found in 82.91% of patients. Vitamin D insufficiency (53.38%) was the most prevalent, followed by osteopenia (44.38%), impaired renal function (26.69%), and osteoporosis (17.45%). Risk factors of vitamin D insufficiency are age ≥71 years (OR 0.33, P = 0.003) and bilateral affected side (OR 1.99, P = 0.007). For osteopenia and osteoporosis, risk factors were age, body mass index, affected side, and chronic kidney disease ( P < 0.05). Discussion In the aspect of Vit D insufficiency, age>70 and bilateral OA knee were significantly related in many ways, such as reduction in cutaneous synthesis and daily exposure to sunlight and various diseases, including CKD and GI malabsorption. The risk factors of osteopenia and osteoporosis can be explained throughout several mechanisms. For instance, abnormality in hormone and cytokines metabolism will lead to the increase in adipocyte differentiation and fat accumulation. And that situation may lead to the decrease in osteoblast differentiation and increased osteoclast activity which could lead to negative impact on bone strength. Conclusions Metabolic bone diseases were common in most patients with OA knee, and the insufficiency in amount of vitamin D(serum 25-hydroxyvitamin D), osteoporosis, and osteopenia conditions were mainly identified. These preventable conditions have risk factors that are mostly correctable These preventable conditions have risk factors that are mostly correctable, for example gain more outdoor activities, consume vitamin D supplement or start osteoporosis treatment program. Further analysis is necessary to establish solid evidence in the comparison of risk factors between the OA and non-OA groups.